Precision therapy targeting CAMK2 to overcome resistance to EGFR inhibitors in FAT1-mutated oral squamous cell carcinoma - Yumeng Lin; Yibo Huang; Bowen Yang; You Zhang; Ning Ji; Jing Li; Yu Zhou; Ying-Qiang Shen; Qianming Chen; Xiangxiang Pan (Chinese Medical Journal)
Abstract. Background:. Oral squamous cell carcinoma (OSCC) is a prevalent type of cancer with a high mortality rate in its late stages. One of the major challenges in OSCC treatment is the resistance to epidermal growth factor receptor (EGFR) inhibitors. Therefore, it is imperative to elucidate the mechanism underlying drug resistance and develop appropriate precision therapy strategies to enhance clinical efficacy. Methods:. To evaluate the efficacy of the combination of the Ca2+/calmodulin-dependent protein kinase II (CAMK2) inhibitor KN93 and EGFR inhibitors, we performed in vitro and in vivo experiments using two FAT atypical cadherin 1 (FAT1)-deficient (SCC9 and SCC25) and two FAT1 wild-type (SCC47 and HN12) OSCC cell lines. We assessed the effects of EGFR inhibitors (afatinib or cetuximab), KN93, or their combination on the malignant phenotype of OSCC in vivo and in vitro. The alterations in protein expression levels of members of the EGFR signaling pathway and SRY-box transcription factor 2 (SOX2) were analyzed. Changes in the yes-associated protein 1 (YAP1) protein were characterized. Moreover, we analyzed mitochondrial dysfunction. Besides, the effects of combination therapy on mitochondrial dynamics were also evaluated. Results:. OSCC with FAT1 mutations exhibited resistance to EGFR inhibitors treatment. The combination of KN93 and EGFR inhibitors significantly inhibited the proliferation, survival, and migration of FAT1-mutated OSCC cells and suppressed tumor growth in vivo. Mechanistically, combination therapy enhanced the therapeutic sensitivity of FAT1-mutated OSCC cells to EGFR inhibitors by modulating the EGFR pathway and downregulated tumor stemness-related proteins. Furthermore, combination therapy induced reactive oxygen species (ROS)-mediated mitochondrial dysfunction and disrupted mitochondrial dynamics, ultimately resulting in tumor suppression. Conclusion:. Combination therapy with EGFR inhibitors and KN93 could be a novel precision therapeutic strategy and a potential clinical solution for EGFR-resistant OSCC patients with FAT1 mutations.